GEN VITELLOGENIN (VTG) PADA IKAN NILEM (OSTEOCHILUS VITTATUS VALENCIENNES, 1842): PARSIAL SEKUENS DAN EKSPRESI GEN DIFERENSIAL PASCA PEMIJAHAN SETELAH INDUKSI ESTRADIOL-17? - Aulia Rufiatin Nisa', Silmy
Vitellogenesis as one of the important stages in oocyte growth, characterized by yolk protein synthesis and its accumulation in the ooplasma. Vtg plays an important role in oocyte hydration and precursor for yolk protein as the main source of nutrition for developing embryos. Vtg is also the main factor for completed oocyte growth and good egg quality. The synthesis of Vtg is encoded by the vtg gene expressed in hepatocyte cells and controlled by FSH and Estradiol-17-? (E2). Previous research in several fish belonging to the Cyprinidae family, has classified the Vtg proteins into three types, namely VtgAa, VtgAb, and VtgC. This research was conducted with the aim of studying the structure of the vtg gene and partial segments of the vtg gene for Bonylip barb fish, and to studying the expression of the vtg gene for post-spawning Bonylip barb fish using E2 induction. A total of 60 mature female Bonylip barb (weight 80-120 g) were divided into five groups: (1) Control group (K0), (2) Vehicle control group (K1), the fish were injected with E2 solvent (olive oil), (3) Treatment group 1 (P1), fish were injected with E2 dose of 105 ?g/kg BW, (4) Treatment group 2 (P2), fish were injected with E2 dose 210 ?g/kg BW, and (5) Treatment Group 3 , fish were injected with E2 dose of 420 ?g/kg BW (P3). E2 injection was performed intraperitoneally. Sampling were performed on days 1st, 15th, 29th, and 43rd after E2 injection. Liver and ovarian tissue were isolated, stored in Eppendorf tubes, frozen in liquid nitrogen and storage at -80°C. Total RNA isolation and Reverse Transcription-Polymerase Chain Reaction (RT-PCR) were carried out on liver tissue using the commercial kit method. Oligoprimers were designed based on the vtg gene sequences of Zebrafish, Ctenopharyngodon idella, and Gobiocypris rarus downloaded from GenBank. Electrophoresis was carried out on 1% agarose gel and sequencing was carried out at First Base Laboratories, Malaysia. The resulting sequences were analyzed using Finch TV DNA Baser, BLAST, Expasy, and CDD. Semi-quantitative measurement of vtg gene expression was carried out by isolating Total RNA in liver and ovarian tissue, reverse transcription, and Real-Time qPCR. The ??Ct method was used to analyze the Ct values of target and reference genes. From the sequencing results, the nucleotide sequences were obtained in the vtg1, vtg2, and vtg3 genes. The target length of the vtg1 gene amplified was 305 bp, vtg2 was 270 bp, and vtg3 was 290 bp. The phylogenetic tree was created using MEGA 6.0 with the Maximum Likelihood (ML) method with a bootstrap value of 1000 and the Bayesian method. The vtg1 and vtg2 genes in Bonylip barb are in one cluster, while the vtg3 genes are located in different clusters. The results of the analysis using the Bayesian method shown that vtg3 had the greatest difference in genetic variation between vtg1, vtg2, and vtg3. The alignment results of the three amino acid sequences showed that Bonylip barb had a conserved and specific Vtg domain, namely Vitellogenin-N. Measurement of vtg gene expression was carried out using primers from the vtg1 and vtg2 genes. Statistical tests on gene expression data were performed using the Kruskal-Wallis non-parametric test and the Bonferroni test. The measurement results normalized by the expression of the ?-actin gene shown that administration of E2 increased the expression of vtg1 and vtg2 in the liver, but the dose of E2 did not give significantly results. The expression of the vtg1 gene in the liver increased until the 29th day, but the vtg2 gene expression increased until the 43rd day. The dynamic pattern of vtg1 and vtg2 gene expression in the ovary is possibly due to the involvement of factors beside E2 that play roles in the regulation of vtg gene expression, such as ERE and transcription factors. Keywords: bonylip barb, gene expression, Vtg, Estradiol-17?, qPCR